Preparation of graphene-polypyrrole and graphene-polypyrrole-manganese oxide nanocomposites as electrochemical supercapacitor electrode - Lim, Yee Seng (2013)
Electrode material with high capacity performance is indispensable for realizing high performance supercapacitors. Hence, the key aspect for improving the performance of supercapacitors is to improve the capacity performance of the active materials. The work present herein focuses on the synthesis, electrochemical capacity performance of the graphene-based nanocomposite materials for supercapacitors, and elucidation of the physical factors which contribute towards the observed capacity performance. This research work was divided into four parts. An initial study was focuses on synthesis of polypyrrole/graphene (PPy/GR) hybrid materials. A one-step electrochemical deposition has been employed to synthesize binary nanocomposite films of PPy/GR. The bulbous surface of polypyrrole (PPy) and the almost transparent tissue-like GO nanosheets were replaced by new appearance of the nanocomposite where the surface was flat but creased. The electrical conductivity of the PPy/GR nanocomposite was higher than that of the pure PPy film, based on the electrical conductivity study measured with a four point probe. The high electrical conductivity of PPy/GR nanocomposite film demonstrated its potential application as supercapacitor electrode. The second part of the work was to evaluate the capacitive performance of synthesize PPy/GR nanocomposite films. Studies showed that PPy/GR electrode displayed better capacitive performance than that of pure PPy, reflecting a synergistic effect between PPy and GR, as analysed by a three electrode electrochemical experiment. The electrochemical results revealed that the capacitive performance of PPy/GR nanocomposites depended on deposition parameters such as concentration of pyrrole and GO, deposition time and deposition potential. The third part of the work was investigated the integration of additional nanostructure metal oxide, specifically manganese oxide into PPy/GR nanocomposite to maximise the electro-active surface area accessible to electrolyte ions. An increase of capacity performance (up to 320.6 Fig) was observed through the integration of manganese oxide, which is attributed to the morphology of polypyrrole/graphene/manganese oxide (PPy/GRIMnOx) ternary composite maximize the pseudocapacitive contribution from redox-active Mnf), and PPy and EDLC contribution from individual GR sheets. The final studies sought to focuses on control of size, morphology, quantity and distribution of PPy particles in the nanocomposite matrix, aimed at fully harness the capacitive performance of functional components and improving the pore accessibility of graphene. In this study, FeCb catalyst was used to control the particle size of polypyrrole coated on GR aimed to avoid polymeric agglomeration. The improved capacitive performance (797.6 Fig) was attributed to the controlled particle size of polypyrrole growth on individual GR sheets and overlap of GR sheets forming a highly open structure provides easier access of electrolyte into composite film maximize the pseudocapacitive contribution from redox-active polypyrrole and EDLC contribution from individual GR sheets.